A Study of Non-Isothermal Decomposition of Calcium dl-Lactate Pentahydrate - Verma, B.P.; Verma, R.K.; Chandra, M.; Pandey, S.P.; Mallick, A.K.; Verma, Lata (Asian Journal of Chemistry, 2012)
The thermal decomposition of calcium dl-lactate pentahydrate has been studied under non-isothermal conditions in static air atmosphere with heating rate programmed at 1/6 Ks–1. The thermogravimetric data thus obtained have been analysed for the kinetic parameters of the two decomposition steps using Freeman-Carrol, Horowitz-Metzer, Coats Redfern, Fuoss, Karkhanawala-Dharwakar and Zsako methods. Decomposition mechanisms have also been suggested.